Design and Analysis of a Hybrid-Excited Doubly Salient Generator With Symmetric Phases Based on Long Pitch Field Sources - Gao, Mengzhen; Yang, Xiangyu; Cao, Jianghua; Jiang, Siyuan; Zhao, Shiwei; Zhang, Zifan (IEEE transactions on energy conversion, 2024)
To solve the asymmetric problems of each phase caused by the different relative positions of the armature coils and excitation sources (PMs and excitation coils) in traditional three-phase hybrid-excited doubly salient generator (HEDSG), a novel HEDSG with long pitch field sources is proposed in this paper. Because of the adoption of excitation winding wound around the PMs sandwiched "four-teeth", the symmetric magnetic circuits among phases can be achieved, thus the balanced three-phase back electromotive force (EMF) curves can be obtained. First, the configuration of proposed HEDSG is described, based on which its operation principle is discussed from the perspective of magnetic circuits. Besides, the flux regulation principle is analyzed based on the simplified equivalent magnetic circuit model. Then, a multi-step design optimization method is implemented to determine optimal structural parameters. Whereafter, the effect of the bidirectional excitation on the static and dynamic performances of the proposed HEDSG is investigated, which demonstrates it has a strong flux regulation ability. Furthermore, a comparative study between the proposed and traditional HEDSGs is conducted. It is shown that the proposed HEDSG can essentially solve the asymmetric problem among phases and possesses the merits of lower cogging torque and higher output power. Finally, a prototype of the proposed HEDSG is fabricated and tested so as to experimentally verify the analysis and simulation.